ANALISIS KEMAMPUAN MEMBERIKAN ALASAN DAN MENGINTERPRETASI SUATU PERNYATAAN - Wuny Noviyanti; Ila Rosilawati; Tasviri Efkar (Universitas Lampung, 2013)
Students who have different levels of cognitive ability then were given the same learning matery, those the critical thinking skills will be appropriate with the level of their cognitive ability. This research aimed to describe the ability of giving reason and interpreting a statement on the acid-base matery through the application of LC3E in each group. The subject in this research was students of Grade XI Sains 4 Senior High School 12 Bandar Lampung Academic Year 2012/2013. This research was a descriptive research, used the pre-experimental method with a one-shot case study design. Data analysis used descriptive analysis. Based on the result of data analysis summarized that ability of giving reason in high level group: almost all were excellent and the others were good. In intermediate level group, almost all were good and the others were excellent. In low level group, almost all were good and the others were good enough. The ability of interpreting a statement in high level group: half were excellent, almost half were good, and the others were good enough. In intermediate level group, just small part were excellent, almost half were good and the others were good enough. In low level group, almost were good and the others were good enough.Kata kunci: memberikan alasan, menginterpretasi suatu pernyataan, kelompok tinggi, kelompok sedang, kelompok rendah